Alat Pengering Biopelet Tipe Rak Dengan Daya 500 Watt - Kamal, Dianta Mustofa; Heryana, Ghany (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2023)
Drying of biopellets is currently still using the conventional method, namely by drying directly under the hot sun. This method is not optimal when the weather is rainy or cloudy, and requires a large area of land. Based on these problems, the purpose of this study was to test the performance of the biopellet dryer and determine the drying time to reach the moisture content in accordance with SNI 8021:2014. The test was carried out by drying 5.000 grams of biopellet samples and seeing the average of the final mass. The average final mass of each test sequentially is 4,785 grams, 4,581 grams, 4,385 grams, 4,016 grams, 3,804 grams, and 3,595 grams. The reduction in water content obtained within 180 minutes was 28.12% with the initial water content in biopellets of 40%. The total water content obtained from the drying is 11.88%. Performance of the biopellet dryer with the power used by this biopellet dryer is 500 Watt. Capable of drying 5.000 grams biopellet with an initial moisture content of 40%. Room temperature is 120°C with a drying rate of 468.667 Gram/hour. Dry biopellet within 180 minutes with a moisture content of 11.88% according to the standard of SNI 8021:2014.  Keywords: Biopellet Drying, Dryer, Moisture Content, Power